Carga de trabalho mental: análise crítica dos métodos de avaliação - Silva, Tiago Machado e (2018)
The mental workload (MW) is characterized as a reflection of mental stress, depending on the task performed, the environment and the specific operating conditions, along with the worker's ability to respond to these demands. The analysis of the MW depend on the application of specific tools or methods, which may vary depending on the specific context of the application, the type of worker analyzed, the country of application, the availability of resources and/or the ergonomist. The main goal of the present study was to perform a critical analysis of the tools used to evaluate the mental workload. For this, a systematic review of the literature was carried out in articles published in the period from 2000 to 2017 available in the electronic databases ScienceDirect, Scopus and Web of Science, which involved a bibliometric analysis and the contents of the selected portfolio. The results compiled 85 articles aligned with the objectives and criteria established in the research, of which the authors, journals, keywords, tools used, workers analyzed and countries of research application were highlighted. The most prominent journal was "Ergonomics" and the main keywords found were "mental workload", "workload" and "NASA-TLX". The most used methods were the analysis of physiological measurements and NASA-TLX, out of 22 found. The main workers studied were health workers, pilots and air traffic controllers and 35% of the studies were performed in the United States. The 22 tools were classified into physiological measures, performance measures and subjective measures, which were further labeled in multidimensional and one-dimensional subjective measures. Physiological measures, performance measures and some one-dimensional subjective measures can be measured continuously and in real time, accompanying variations in mental workload, and it is not depending on the participants' memory. The multidimensional subjective measures provide a diagnosis about the various dimensions of the MW, are the most used tools, are applied after the procedures and are not intrusive. Physiological measurements have more expensive and complex procedures, performance measures may be intrusive, one-dimensional subjective measures provide only a general score for the workload and multidimensional subjective measures have longer procedures and are dependent on worker memory. The vast majority of tools have no country limitation or application in workers and work situations. Thus, the criterion for choosing the method depends on the work situation, the objectives of the analysis and the available resources, and it is indicated to use at least two methods categorized differently to increase the validity of the results, idealizing an analysis with the three categories.